2023
DOI: 10.3390/ani13101593
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Two Mitogenomes of Hyla sanchiangensis (Anura: Hylidae), with Phylogenetic Relationships and Selection Pressure Analyses of Hylidae

Abstract: Hyla sanchiangensis (Anura: Hylidae) is endemic to China and is distributed across Anhui, Zhejiang, Fujian, Guangdong, Guangxi, Hunan, and Guizhou provinces. The mitogenomes of H. sanchiangensis from two different sites (Jinxiu, Guangxi, and Wencheng, Zhejiang) were sequenced. Phylogenetic analyses were conducted, including 38 mitogenomes of Hylidae from the NCBI database, and assessed the phylogenetic relationship of H. sanchiangensis within the analyzed dataset. Two mitogenomes of H. sanchiangensis showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…Research has already demonstrated that the 13 PCGs within the mt genome may be subject to positive selection under the influence of low temperatures [57,118]. In the present study, we found that the 258th site in ATP8 and the 2265th site in ND2 had higher evolutionary rates using the site model, which utilizes various site class-specific models and assumes that all branches have the same ω ratio but differ among sites in alignment [100].…”
Section: Positive Selection Analysissupporting
confidence: 51%
“…Research has already demonstrated that the 13 PCGs within the mt genome may be subject to positive selection under the influence of low temperatures [57,118]. In the present study, we found that the 258th site in ATP8 and the 2265th site in ND2 had higher evolutionary rates using the site model, which utilizes various site class-specific models and assumes that all branches have the same ω ratio but differ among sites in alignment [100].…”
Section: Positive Selection Analysissupporting
confidence: 51%
“…To further understand the role of selective pressure on the mitochondrial PCGs among the Muscicapidae species, we calculated and compared the average Ka/Ks ratio for each PCG (Figure 6B). Ka/Ks ratio = 1 denotes neutral mutations, Ka/Ks ratio < 1 denotes negative selection, and Ka/Ks ratio > 1 denotes positive selection [82,83]. Here, the average Ka/Ks ratio for all PCGs were consistently far lower than 1, indicating that all PCGs of Muscicapidae mitogenomes had experienced purifying selection.…”
Section: Nucleotide Composition Diversity and Evolutionmentioning
confidence: 85%
“…A non-coding region with a length of about 35 bp was found between trnS1 and ND5 in the five Hylidae sequences evaluated in this study. This non-coding region has been found in many species of Hylidae [ 62 , 63 , 64 , 65 , 66 , 67 , 68 ], but did not exist in D. versicolor [ 54 ]. Whether this is the feature of all members of Hylidae will require more sequences to be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there are many more species that show genetic differences in ND gene expression in response to various stresses. The proteins encoded by these genes are concentrated in mitochondrial complex I, and positive selection sites in previous studies were also concentrated mostly in mitochondrial complex I [ 65 ]. Mitochondrial complex I is a large enzyme and is the main entry point for electrons delivered from nicotinamide adenine dinucleotide (NADH) into the respiratory chain [ 72 ].…”
Section: Discussionmentioning
confidence: 99%